Comparison of adjuvant treatment regimens for high-risk hepatocellular carcinoma: a Bayesian network meta analysis and systematic review - Li, Jiahao; Liu, Yingnan; Qiu, Yuqi; Qu, Chao; Li, Jiarui (Frontiers in Immunology, 2024)
BackgroundThe five-year recurrence rate for patients with hepatocellular carcinoma (HCC) is as high as 70%. Patients with high-risk recurrence factors experience significantly poorer prognosis. Local regional therapies, including transarterial chemoembolisation (TACE), hepatic arterial infusion chemotherapy (HAIC), radiotherapy, and emerging immunotherapy, are commonly used adjuvant treatment options. We conducted an indirect comparison of these adjuvant therapies for such patients.MethodsWe conducted a systematic search in public databases for relevant studies and assessed the efficacy and safety of the corresponding therapies by consolidating disease-free survival (DFS), overall survival (OS), and adverse events (AEs).ResultsA total of eight randomised controlled trials were ultimately included. The Gelman-Rubin plot and kernel density estimation indicate that the stability of the combined model is satisfactory.Conclusionimmunotherapy is not inferior to local regional therapies in delaying tumour recurrence, however, the higher incidence of AEs remains a significant concern. Adjuvant radiotherapy demonstrated superior efficacy in delaying tumour recurrence compared to adjuvant TACE, although further support from phase III clinical trial evidence is required.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024576316.